2005
DOI: 10.1037/0278-7393.31.6.1281
|View full text |Cite
|
Sign up to set email alerts
|

Word Learning and Individual Differences in Word Learning Reflected in Event-Related Potentials.

Abstract: Adults learned the meanings of rare words (e.g., gloaming) and then made meaning judgments on pairs of words. The 1st word was a trained rare word, an untrained rare word, or an untrained familiar word. Event-related potentials distinguished trained rare words from both untrained rare and familiar words, first at 140 ms and again at 400-600 ms after onset of the 1st word. These results may point to an episodic memory effect. The 2nd word produced an N400 that distinguished trained and familiar word pairs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
169
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 26 publications
(29 reference statements)
19
169
1
Order By: Relevance
“…For example, Swanborn and de Glopper (2002) showed that in a group of 223 children, participants with low reading comprehension scores learned fewer words from context than peers with high comprehension scores. This finding is consistent with data showing that poor comprehenderschildren who have reading comprehension impairments despite the ability to read words and texts at an age-appropriate level-are poor at inferring the meaning of new words from context (Cain et al, 2003;Cain, Oakhill, & Lemmon, 2004;Oakhill, 1983) and remembering them over time (Nation, Snowling, & Clarke, 2007;Ricketts et al, 2008; for a similar finding with adults see Perfetti, Wlotko, & Hart, 2005).Reading experience enables vocabulary development, with measures of print exposure predicting vocabulary growth (e.g., Echols, West, Stanovich, & Zehr, 1996). Equally though, existing vocabulary knowledge is a significant predictor of semantic learning following reading (e.g., Cain et al, 2004;Ewers & Brownson, 1999;Sénéchal, Thomas, & Monker, 1995;Shefelbine, 1990).…”
supporting
confidence: 79%
“…For example, Swanborn and de Glopper (2002) showed that in a group of 223 children, participants with low reading comprehension scores learned fewer words from context than peers with high comprehension scores. This finding is consistent with data showing that poor comprehenderschildren who have reading comprehension impairments despite the ability to read words and texts at an age-appropriate level-are poor at inferring the meaning of new words from context (Cain et al, 2003;Cain, Oakhill, & Lemmon, 2004;Oakhill, 1983) and remembering them over time (Nation, Snowling, & Clarke, 2007;Ricketts et al, 2008; for a similar finding with adults see Perfetti, Wlotko, & Hart, 2005).Reading experience enables vocabulary development, with measures of print exposure predicting vocabulary growth (e.g., Echols, West, Stanovich, & Zehr, 1996). Equally though, existing vocabulary knowledge is a significant predictor of semantic learning following reading (e.g., Cain et al, 2004;Ewers & Brownson, 1999;Sénéchal, Thomas, & Monker, 1995;Shefelbine, 1990).…”
supporting
confidence: 79%
“…Neural changes associated with reading acquisition have also been well documented under both natural (e.g., Brem et al, 2006;Burgund et al, 2006;Maurer et al, 2005bMaurer et al, , 2006 and experimental conditions (e.g., Brem et al, 2005;Chen et al, 2007;McCandliss et al, 1997;Perfetti et al, 2005;Xue et al, 2006). Nevertheless, there is little consensus with regard to the exact mechanisms underlying these neural changes.…”
Section: Introductionmentioning
confidence: 98%
“…Such a trace is detectible in ERPs, which can differentiate between a recently learned word and a familiar or unfamiliar word as early as 140 ms, with an additional later component between 400 and 600 ms that is also sensitive to comprehension skill. The later component is more pronounced in skilled comprehenders, indicating that skilled readers are more effective in establishing strong episodic traces for new words (Perfetti, Wlotko, & Hart, 2005). With repeated exposures to a new word, and multiple episodic traces, a reader should be able to establish a new lexical entry, more independent from the individual episodic traces, complete with semantic, phonological, and orthographic information.…”
Section: Differences Between Print and Speech In Learning New Wordsmentioning
confidence: 99%